2014
DOI: 10.3748/wjg.v20.i18.5519
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for liver-related mortality in chronic hepatitis C patients: A deceased case-living control study

Abstract: This study indicates that interferon-α treatment, the stage at the initial diagnosis of the disease and comorbidities are all independent risk factors for liver-related mortality in CHC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Hepatic fibrosis often occurs and evolves dynamically in the natural course of chronic HCV infection. The presence of advanced fibrosis or cirrhosis has long been recognized as an independent and the most relevant predictor of mortality and server complications in chronic hepatitis C (CHC) patients . On the other hand, a rapid and significant regression of liver fibrosis or cirrhosis may reduce the risk of end‐stage liver disease and hepatocellular carcinoma .…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic fibrosis often occurs and evolves dynamically in the natural course of chronic HCV infection. The presence of advanced fibrosis or cirrhosis has long been recognized as an independent and the most relevant predictor of mortality and server complications in chronic hepatitis C (CHC) patients . On the other hand, a rapid and significant regression of liver fibrosis or cirrhosis may reduce the risk of end‐stage liver disease and hepatocellular carcinoma .…”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐one studies were identified which evaluated the risk of developing DM in HCV‐infected individuals (N = 22 432 including n = 3583 with DM); 14 of them also included a non‐HCV control group . Seven studies were from Japan, three studies from China, one study from Korea, one study from multiple countries, and nine studies were from Taiwan; eighteen studies were cross‐sectional, one was case‐control, and two were prospective cohort studies of incidence of de novo DM (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…HCC screening was performed at least every 2 months after the SVR. HCC was confirmed by liver histopathology, at least two imaging tools, or by one imaging diagnostic modality and a serum AFP level of 400 ng/mL or higher 11,12. Alcohol consumption was defined as alcohol consumption on at least 4 days per week for at least 5 years 11,12.…”
Section: Methodsmentioning
confidence: 99%
“…HCC was confirmed by liver histopathology, at least two imaging tools, or by one imaging diagnostic modality and a serum AFP level of 400 ng/mL or higher 11,12. Alcohol consumption was defined as alcohol consumption on at least 4 days per week for at least 5 years 11,12. Ever smokers were defined as patients who had smoked cigarettes at least 4 days per week for at least 5 years 11,12.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation